An innovative drive-through approach for structural testing and experimental insights from two cable stayed bridges - Seyedmilad Komarizadehasl; Zhouhui Shen; Ye Xia; Mingming Song; Jose Turmo (Developments in the Built Environment)
Effective monitoring of bridge infrastructure is essential for ensuring safety, reliability, and longevity. Traditional Structural Health Monitoring (SHM) methods have been challenged by installation complexity, maintenance demands, and high costs, particularly in large-scale or long-span bridges. In response, a novel, non-intrusive drive-through method for extracting bridge eigenfrequencies has been developed using vehicle-multi-mounted Micro-Electro-Mechanical Systems (MEMS) sensors. A passing vehicle is thereby converted into a mobile sensing platform, and bridge dynamic properties are captured under normal traffic conditions. Experimental validation was conducted on Shanghai's Yangpu and Nanpu cable-stayed bridges, and eigenfrequency extraction from a single crossing was demonstrated, significantly reducing the need for multiple passes. The signal-to-noise ratio was improved by the fusion of data from multiple sensors, and frequency identification was achieved. A practical and cost-effective solution for large-scale bridge monitoring is thus offered, and further work is planned to extend the methodology to additional structural parameters and enhanced robustness.